C24. Cardioembolic Stroke due to LV Thrombus : Very High Risk NSTEMI Complication. (23rd November 2021) - Valdy, Gerry; Syafri, Masrul; Syukri, M
Abstract: Background: Ischemic heart disease is the major cause to the high mortality rate. Ischemic heart disease was responsible for 7 million of the 53 million deaths reported in 2010. Left ventricle thrombus that complicates acute myocardial infarction (AMI) is a major cause of cardioembolic stroke. Case Summary: A 69-year-old man presented with typical of infarction chest pain and shortness of breath since 2 days before admission to the hospital. The patient was diagnosed with NSTEMI TIMI 4/7 GS 177, PVC Frequent and history of VT and was planned for immediate PCI. After cannulation in the left coronary artery, the patient developed VT/VF and therefore CPR was performed. The patient was in ROSC then admitted to the CVCU and had improved. After two days of treatment, the patient experienced weakness in right limbs and difficulty of speaking, followed by decreased consciousness and suspected with ischemic stroke. The patient was then immediately treated for cardioembolic stroke. After 1 day of treatment the patient got worsened and was declared dead. Discussion: Based on NSTEMI startification, patients was included in very high risk with a major cardiovascular event rate of 40.9%. During the treatment, patients experiencing cardioembolic stroke which causes increased mortality. Management of cardioembolic stroke as soon as possible increases the chances of success in therapy